1994
DOI: 10.1111/j.1365-2990.1994.tb00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptors in the Parkinsonian midbrain

Abstract: Several hypotheses have been put forward to explain the pathogenesis of Parkinson's disease (PD) and recently it has been suggested that alterations in iron homeostasis may be implicated. Because of the central role of the transferrin receptor in providing access of iron to cells, we have studied the distribution and density of transferrin receptors using [3H]-transferrin ([3H]-Tf) binding and tritium film autoradiography in the normal and PD midbrain. High levels of [3H]-Tf binding were found in the dorsal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…This approach revealed that genes affected by disease but not gender were involved several cellular processes such as transmission of nerve impulse, synaptic transmission, cell-cell signaling, establishment of localization, localization, transport (Fig 3). Among the genes that exhibit gender-independent altered expression in PD are: neuronal beta-catenin, which has been implicated in Alzheimer disease and synaptic plasticity (Fuentealba et al, 2004;Goda, 2002); PAEL-R, a protein accumulated in Lewy bodies (Murakami et al, 2004) and a potential parkin substrate (Nakahara et al, 2003;Yang et al, 2003); kallikrein 6, involved in ASYN degradation (Iwata et al, 2003); and transferrin, which may be related to iron deposition observed in PD brain (Morris et al, 1994).…”
Section: Microarray Resultsmentioning
confidence: 99%
“…This approach revealed that genes affected by disease but not gender were involved several cellular processes such as transmission of nerve impulse, synaptic transmission, cell-cell signaling, establishment of localization, localization, transport (Fig 3). Among the genes that exhibit gender-independent altered expression in PD are: neuronal beta-catenin, which has been implicated in Alzheimer disease and synaptic plasticity (Fuentealba et al, 2004;Goda, 2002); PAEL-R, a protein accumulated in Lewy bodies (Murakami et al, 2004) and a potential parkin substrate (Nakahara et al, 2003;Yang et al, 2003); kallikrein 6, involved in ASYN degradation (Iwata et al, 2003); and transferrin, which may be related to iron deposition observed in PD brain (Morris et al, 1994).…”
Section: Microarray Resultsmentioning
confidence: 99%
“…However, two regional analyses of radiolabeled ferrotransferrin binding sites in the mesencephalon have shown that their density was extremely low in the SNpc of controls and was either unchanged or decreased in PD patients (13,14), which indicates that the increase in nigral iron content reported in surviving neurons (4,8,11) and in glial cells (7) may occur (i) by metabolic changes with a higher penetration of iron without any increased density of transferrin receptors on the soma of DA cells, (ii) by receptors located on other parts of DA neurons (i.e., terminals), and/or (iii) by other pathways. A localization of transferrin receptors on DA terminals in the striatum has been suggested by studies of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated mice (15) or MPTPtreated monkeys (16) and human brains taken at postmortem (15,16), but this still needs to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion of this endo sóme with an acidic compartment within the cell causes the dissociation of iron from transferrin and the entry of iron into the cell cytoplasm. The transferrin, still bound to its receptor, is then returned to the cell surface where dissocia-tion occurs, leaving the extracellular transferrin free to bind more iron |1], A specific transport route for iron to the brain, which utilizes transferrin, has been suggested [2], Iron delivered to the brain by this mechanism is used mainly in the synthe sis of iron-containing enzymes in the mitochondrial respira tory chain, essential for cellular energy production; excess iron is stored within the protein ferritin [3], Transferrin is synthesized within the brain, transferrin mRNA being localized chiefly within oligodendrocytes [4] and also the choroid plexus [4,5], Immunocytochemical studies in the rat brain have shown that transferrin is localized within oli godendrocytes. with little reactivity in other cell types [6], In the developing mouse [7] and human brain [8.…”
Section: Introductionmentioning
confidence: 99%